Development of Hots-Based E-Worksheets for Arabic Grammar Course in Department of Arabic Language Education - Kamaluddin Kamaluddin; Lathifah Al Husna; Nurlaila Nurlaila; Amelia Amelia; Izzuddin Musthafa; Suliman Hassan Suliman Elwarfali (Ta'dib, 2022)
The purpose of this research is to produce a valid and practical Arabic grammar e-worksheet for university students based on Higher Order Thinking Skills (HOTS). The research type is Research & Development (R&D) with the Instructional Development Institute (IDI) model. Research data were collected through questionnaires and documentation. The data obtained from the validity and practicality questionnaires were tabulated for each component of the assessment and then the average score was calculated and converted into qualitative data. Documentation technique is done by analyzing documents in the form of syllabus, materials, and literatures. The results of this research and development show that the developed Arabic grammar e-worksheet is stated to be very valid with an average validity score of 4.35 and very practical with an average practicality score of 4.8. Based on the results, it is hoped that the lecturers will be able to use the developed e-worksheet in the Arabic grammar course, because it can facilitate students' higher-level thinking skills.